Analisis Pengaruh Kurs, Suku Bunga dan Return Saham Terhadap Aktivitas Volume Perdagangan - calista maxenchio Teja; Lia Dama Yanti (Komunitas Dosen Indonesia, 2023)
The analysis technique uses the Multiple Linear Regression method using the SPSS 25 program. The results of the statistical analysis reveal that first, the exchange rate variable has no effect on Trading Volume Activity, this is indicated by a significance value of 0.371 > 0.05 and a t count value of 0.897 < t tabel 1,98238. Second, the interest rate variable has an effect on trading volume activity, this is indicated by a significance value of 0.025 < 0.05 and t count -2.273> t table 1.98238. Third, the variable Stock Return has no effect on Trading Volume Activity, this is indicated by a significance value of 0.571 > 0.05 and a t count value of 0.880 <t table 1.98238. Simultaneously the exchange rate, interest rate, and stock return variables affect trading volume activity, this can be shown by the calculated F value of 3.777 > F table 3.08 with a significance level of 0.013 <0.05.